Analysis of Spirituality Effect on Workplace and Work Motivation on Employee Performance Bank Syariah Mandiri in Jawa Barat Region - usep deden suherman (Li Falah: Jurnal Studi Ekonomi dan Bisnis Islam, 2020)
This study aims to determine how much influence spirituality in the workplace on the performance of Bank Syariah Mandiri Bank employees in the West Java Region how much influence the motivation of work on the performance of Bank Syariah Mandiri employees in the West Java Region and how much power the Spirituality at work and work motivation simultaneous performance of Bank Syariah Mandiri employees in the West Java Region. This study uses a quantitative approach with the primary data collection tool questionnaire. The sampling technique used was the purposive sampling technique. While the data analysis technique used is multiple regression analysis. The study results illustrate that Spirituality at work has a positive and significant influence on employee performance. Then work motivation has a positive and significant effect on employee performance. Furthermore, Spirituality at work and work motivation together have a positive and significant impact on employee performance.